APLIKASI KEUANGAN SEDERHANA RUMAH YATIM DAN QUR’AN MADANI BERBASIS WEBSITE DENGAN FRAMEWORK CODEIGNITER: STUDI KASUS PADA RUMAH YATIM DAN TAHFIDZ QUR’AN MADANI BANDUNG - Faisal Mufid; Novita Anggraini (Melati Institute, 2023)
Final project research is carried out as one of the requirements before carrying out the preparation of the final project report. research is held in an institution or company that functions as the application of student learning competencies in their field of expertise. As for the agency or company intended to complete or assist the implementation of operational activities. And as for the object is the orphanage and Tahfidz Qur'an madani, this research was carried out in approximately one month. For the results given to the object of research is to design and design a simple website-based financial application with the help of a programming language codeigniter and database which is used is MySQL that will be assigned to the agency. The reason for making this simple website-based financial application is because the company still uses the manual method in the institution's financial recording activities.